The Effect of Personalized Advertising on Purchase Intention: The Mediating Role of Attitude Toward Ads among Shopee Users - Mendrika Ny Hanitra Randrianavo; Vanessa Gaffar; Tutik Inayati (Image : Jurnal Riset Manajemen, 2025)
Technological advances in artificial intelligence and data analytics have enabled e-commerce platforms to deliver highly personalized advertising. However, how consumers psychologically respond to such personalization remains unclear, particularly in emerging markets. Drawing on Privacy Calculus Theory and the Affect Transfer Hypothesis, this study examines the influence of personalized advertising on purchase intention among Shopee users in Indonesia, with attitude toward advertising as a mediating variable. Data were collected from 114 Shopee users using purposive sampling and analyzed using regression and Hayes’ PROCESS mediation analysis. The results indicate that personalized advertising has a significant direct effect on purchase intention and a significant indirect effect through attitude toward advertising, indicating partial mediation. These findings suggest that personalization influences purchasing not only by improving information fit but also by shaping consumers’ cognitive and emotional evaluations of advertising. This study contributes to the personalized advertising literature by demonstrating the mediating role of attitude toward advertising in an emerging e-commerce context. Practically, the results highlight the importance of designing personalized advertising that balances relevance with consumer trust and perceived privacy.